2011
DOI: 10.1590/s1413-86702011000400013
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid disorders in patients with chronic hepatitis C using interferon-alpha and ribavirin therapy

Abstract: Thyroid dysfunction and autoimmune TD were observed during IFN-α and RIB therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…The prevalence of TAs in female patients with chronic HCV infection was higher but was not significant compared with male patients. This observation was consistent with previous studies, which reported that there was no difference between females and males with respect to TAs before treatment (20,26 (27). IgG1 and IgG3 are more capable of binding to monocytes and neutrophils and activating the complement system than IgG2 and IgG4 (28).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The prevalence of TAs in female patients with chronic HCV infection was higher but was not significant compared with male patients. This observation was consistent with previous studies, which reported that there was no difference between females and males with respect to TAs before treatment (20,26 (27). IgG1 and IgG3 are more capable of binding to monocytes and neutrophils and activating the complement system than IgG2 and IgG4 (28).…”
Section: Discussionsupporting
confidence: 93%
“…The patients enrolled in our study (TD and WTD groups) had similar distributions by sex, age, and virological indicators (HCV genotype and viral load). It has been reported that lower ALT and increased TPOAb levels were more commonly found in CHC patients with TD than those without thyroid disorders (19,20). We observed similar trends between TD and euthyroid patients.…”
Section: Discussionsupporting
confidence: 84%
“…Thyroid dysfunction represents one of the commonest endocrine manifestations of chronic hepatitis C infection, exaggerated by interferon based treatment [4]. Changes in thyroid function are common side-effects occurring during antiviral therapy with interferon-alpha (IFN-α).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in thyroid function are common side-effects occurring during antiviral therapy with interferon-alpha (IFN-α). In this way, the spectrum of thyroid diseases range from the production of isolated anti-thyroid antibodies to dysfunctions such as hypothyroidism, Graves' disease (GD), and destructive thyroiditis [4,5]. IFN-α therapy for HCV may induce thyroid changes or dysfunction in 2.5% to 20% of treated patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation